Water-Heat Order Development Dynamics of Salined Ground Road - Kayumov A.D.; Kayumov D.A; Zafarov O.Z. (Genius Journals, 2022)
This article considers the heat and humidity change laws during the year at the highways foot and the water-heat regime processes in it. The heat and humidity order at the road foot was studied, and the research results on the specific heat capacity of the soil, the freezing depth depends on its salinity, elevation, salt amount and quality
Keywords: Lightly soluble salts; water-heat regime; temperature regime; saline soil